Penggunaan Aplikasi Akuntansi Berbasis Android “Si Apik” untuk Menunjang Pelaporan Keuangan UMKM (Studi Kasus Online Shop Kishmay Beauty) - Triyaningsih, Lulus; Masithoh , Dewi (Teewan Journal Solutions, 2025)
Kishmay Beauty is one of the UMKM engaged in selling cosmetic goods online. Kishmay Beauty was established in 2018 and started selling as an official reseller in 2019. This study aims to enable UMKM actors to apply SI APIK application to their companies properly and can produce financial reports that are useful to support the financial reporting of the Kishmay Beauty online shop. The preparation of the reporting carried out is using SI APIK android-based accounting application. With SI APIK application users can create financial reports quickly and easily. SI APIK application that is easy to understand will be useful for Kishmay Beauty online shop. The data used is revenue transactions, namely from the sale of goods and other receipts, for expenditure transactions, namely from the purchase of inventory. The data obtained is then inputted into SI APIK application, then processes the data, and then produces the final result in the form of a financial position report (Balance Sheet). Income statement and cash flow statement. Research from the use of SI APIK application is based on SAK EMKM. The results of the report are in accordance with SAK EMKM. The results of this study indicate that SI APIK application makes it easier to record financial reports, because the results of the application will automatically create financial reports according to the features available in the application. The use of SI APIK application in the Kishmay Beauty online shop is also very easy to understand. So that users have effective time in using it. In addition, users can use other features for their business needs. The author hopes that the application can be used by the Kishmay Beauty online shop in transactions in its business activities.